Effects of clamping umbilical cord on the neonatal viability of puppies delivered by cesarean section - Pereira, Keylla Helena Nobre Pacifico [UNESP]; Correia, Luiz Eduardo Cruz Dos Santos [UNESP]; Oliveira, Elton Luís Ritir [UNESP]; Bouéres, Cristiano Silva [UNESP]; Cyrino, Marina Andrade [UNESP]; Leis Filho, Antônio Fernandes [UNESP]; Cruz, Raíssa Karolliny Salgueiro; Angrimani, Daniel De Souza Ramos [UNESP]; de SOUZA, Fabiana Ferreira [UNESP]; Chiacchio, Simone Biagio [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (Japanese Society of Veterinary Science, 2020)
In human neonates, when the umbilical cord is kept intact postpartum, blood continues to flow to the neonate, but this procedure might be difficult in dogs owing to a shorter umbilical cord and several neonates in a litter. However, it might be possible to detach the placenta and keep the umbilical cord intact, allowing residual blood to flow to the puppies. This study compared the effects of clamping versus no clamping of the umbilical cord in dogs born by cesarean section on neonatal vitality. The puppies were assessed by Apgar and reflex scores. Fifty puppies delivered from 16 bitches were randomly allocated to receive immediate umbilical cord clamping (n=25) or no clamping for at least 3 min after the onset of breathing (n=25). The puppies were assessed during the first 5 min of life and 10 min after the first assessment. The no clamping group showed significantly higher Apgar scores (second assessment, P<0.01) and reflex scores (first and second assessments, P<0.05) than the clamping group, implying higher vitality in the no clamping group. The differences observed between the moments (first versus second assessment) of each group was significant (P<0.01), revealing higher vitality in the second assessment. The results suggest that keeping the umbilical cord intact for at least 3 min after the onset of breathing may contribute to increased vitality in puppies delivered by cesarean section without any negative consequences.
Keywords: Apgar score; Cesarean section; Dog; Neonatal vitality; Umbilical cord